IDENTIFICATION AND VALIDATION OF LEAF RUST RESISTANCE GENES IN SPRING WHEAT (TRITICUM AESTIVUM L. EM. THELL) GENOTYPES USING MOLECULAR MARKERS - NEERAJ KUMAR VASISTHA; B. ARUN; V. K. MISHRA; R. R. SAXESENA; A. K. PANDEY; R. N. AHIRWAR; P. K. SHARMA (The Bioscan, 2014)
The study was aimed to identify leaf rust resistance gene(s) (Lr) with the help of molecular markers that condition leaf rust resistance in selected wheat cultivars from India and CIMMYT origin. For this purpose leaf rust resistance (Lr) gene(s) has been determined in 10 wheat genotypes using linked molecular markers. The presence of different resistance genes like Lr13, Lr34, Lr35, Lr37, Lr39, Lr46, Lr47, Lr50, Lr67 and Lr68 were validated through PCRbased molecular markers such as SSR, STS and CAPS. The presence of Lr13, Lr34, Lr35, Lr37, Lr39, Lr46, Lr47, Lr50, Lr67 and Lr68 in the tested genotypes was confirmed by a unique amplification of molecular markers Xgwm630, csLV34-7DS, Sr39/Lr35, VENTRIUP-LN2, Xgwm210, Xgwm259,PS10, Xgwm382, cfd71 and cs7BLNLR. Of 10 genotypes, the presence of Lr13 gene was present in all wheat genotypes except HUW468. Genotypes, HUW234, HUW468 and Chirya3 showed the presence of 150 bp fragment specific to LR34gene. A single fragment of 512 bp (SCS265) specific to Lr35, Lr37, Lr39, Lr47 and Lr67 were not present in all the 10 genotypes. Lr46 gene is present in all the genotypes except HUW234, Fret2/Tukru/Fret2. Lr50 is present in all the genotypes while Lr68 is only present in three genotypes like HUW510, Waxwing2*/Kiritati, Kiritati/Seri/Rayon.